Penggunaan Bahasa Gaul Pada Zaman Sekarang - Muhammad Luthfan Alkhairi (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The development of today's communicating style leads to a phenomenon in the form of slang lures closely with the present day. The process of communication and social interaction leads to a tendency of a speaker utilizing the potential of language variations. The most effective factor of influence of the shift of language shift is the habit of speaker, the speech partner, the presence of the third speaker, the topic and situational talks and the language usage capabilities based on the level of education both sellers and buyers. This journal tries to analyze some research results on the language shift that occurred in Indonesia.